Tree-Step Experimentation on Embedding Curvature to Rigid Planar materials Through Cut Patterns - Alaçam, Sema; Bacınoğlu, Zeynep; GÜZELCİ, ORKAN ZEYNEL (My University, 2017)
This study presents the outcomes and findings of a three-step experimentation to integrate analog and digital design and modeling techniques, with a particular focus on augmenting the affordance of bending behavior and curvilinearity of rigid planar surface materials. In the scope of the experimentation process, cardboard was used as a material, cutting and bending actions were utilized as techniques and laser cut and visual scripting environment were involved as tools. The potentials of subtractive material techniques such as cut, bend, kerf operations are examined. The experimentation covers hands-on pattern generation, embedment of cut patterns to 2D planar material, re-mapping 2D patterns onto 3D surfaces based on the insights gained in the previous phase and exploration of new 3D free-form surfaces both in physical and digital environments. The three-step experimentation model presented has potentials to contribute to the pedagogical studies focusing on explorative and creative approaches for integrative design formation and fabrication processes.

Este estudo apresenta resultados e descobertas de uma experimentação de três passos para integrar técnicas de modelagem e design analógico e digital, com especial atenção para o aumento do rendimento do comportamento de curvatura e curvilinearidade dos materiais de superfície planar rígidos. No âmbito do processo de experimentação, o papelão foi utilizado como material, as ações de corte e flexão foram utilizadas como técnicas e o corte a laser e o ambiente de script visual foram envolvidos como ferramentas. São examinados os potenciais de técnicas de materiais subtraíveis, tais como operações de corte, curvatura, incisão. A experimentação abrange a geração de padrão, incorporação de padrões de corte ao material plano 2D e remapeamento de padrões 2D em superfícies 3D, com base nos conhecimentos adquiridos na fase anterior e na exploração de novas superfícies de forma livre em 3D tanto em ambientes físicos como digitais. O modelo de experimentação de três passos apresentado tem potenciais para contribuir com os estudos pedagógicos focados nas abordagens exploratórias e criativas para a formação e fabricação de projetos integrativos.
Keywords: Bending; Making; Laser Cut; Digital Fabrication; Material Techniques; Double Curvature; Flexão; Criação; Corte a Laser; Fabricação Digital; Técnicas Materiais; Curvatura Dupla